Cost-effectiveness of companion BRCA testing and adjuvant olaparib treatment in patients with BRCA-mutated high-risk HER2-negative early breast cancer - Nikolova, Silviya; Ma, Wenkang; Sagoo, Gurdeep S.; Punekar, Yogesh; Sheppard, Elizabeth (Frontiers in Oncology, 2025)
Background and objectiveAs the healthcare industry evolves towards precision medicine, methods to assess the value of integrating companion diagnostics in clinical practice through adequate reimbursement levels are becoming essential. Cost-effectiveness analysis is an established tool used to inform the reimbursement of health technologies.MethodsA decision-tree model was developed to estimate the incremental cost-effectiveness of companion BRCA testing and olaparib use versus no testing and the standard of care (SoC) for patients with BRCA-mutated high-risk HER2-negative early breast cancer from a UK NHS/PSS perspective.ResultsBRCA testing combined with treatment with adjuvant olaparib was associated with an incremental cost-effectiveness ratio (ICER) of £49,327 per quality-adjusted life-year (QALY) gained and an ICER of £86,349 per QALY gained for patients with triple-negative breast cancer (TNBC) and human epidermal growth factor receptor 2 negative/hormone receptor-positive (HER2-/HR+) breast cancer, respectively, compared to no testing and treatment with SoC. This difference in ICER is due to significantly improved outcomes for patients with TNBC who were treated with targeted therapy. For both patient subgroups with early breast cancer, testing and olaparib improved patient outcomes and, despite its relatively high cost, the test and treat strategy was deemed to represent an acceptable use of resources.ConclusionsThe advancement of high-throughput sequencing technologies, coupled with the rise of targeted treatments in recent years, has facilitated a shift from conventional medical practices to individualized oncology therapeutic approaches. Our analysis presented the value of combining genetic sequencing and targeted therapy for patients with breast cancer carrying BRCA mutations and also provided the prototype of a testing model that can be utilized to promote precision medicine for better patient outcomes.